Carbon Emissions in Pune Metropolitan Region (PMR) due to Logistics Industries - Kedar Bhagwat; Sameer Gujar; Ankush Kumar Rout; Rishabh Natholia; S. Sanjay; Gurudas Nulkar; Amitav Malik; Siddharth Bhagwat; Shalvi Pawar (Australasian Accounting, Business and Finance Journal, 2023)
The global supply chain is growing and becoming complex as consumer demand increases. Since 2011, the world has seen an alarming increase in vehicular carbon emissions. Today, motor vehicles are estimated to contribute nearly 24 per cent of the world's direct CO2 emissions. With the advent of E-commerce, consumers/customers prefer deliveries being made at their doorstep. Manufacturing must keep up with the demand for more raw materials and would require more trucks to deliver goods and other production factors. These expansions and developments have put significant strain on the environment and sustainability over the years. This, in turn, highlights the importance of sustainability in logistics and green logistics. Many industries are taking various sustainable measures to balance their environmental impact. The transportation and logistics industry is the third largest contributor to carbon emissions (as per ETenergyworld.com). According to the World Economic Outlook (2020) review report, the road freight sector is India's third most CO2-emitting sector. In this study, we have attempted to calculate the carbon emission in the inner and outer cordons of the Pune Metropolitan Region (PMR) due to goods vehicles (logistics). The calculations are carried out for both Heavy Commercial Vehicles (HCV) and Light Commercial Vehicles (LCV). Logistic hub-wise, region-wise, and highway-wise carbon emissions are also calculated in these areas.
Keywords: Carbon Emissions; Logistics; Pune Metropolitan Region; India